Field Development for Shale Gas Reservoir: An Overview of Energy Game Changer - Shuker, Muhannad Talib (2012)
ABSTRACT Consumption of natural gas boosting day by day, new technologies play vital role in the development of the unconventional gas reservoirs and contribute to unlock the gas potential from the shale formation. It combats climate change by consideration of the world demanding secure, abundant and affordable energy. The industry workshops and other sources collected feedback, technology plays today and required to be developing strategy for field development in the unconventional gas reservoirs. For this alter the energy supply picture for potentially the world, experts have called shale gas as “energy game changer”. There are many present challenges and complexities in the shale reservoirs involves control the well placement and locations, mapping, reduces drilling and completion cost, develop stimulation strategies, improve operational efficiencies, and at the same time carefully handle environmental sensitivities. Shale Gas Prediction Model (SGPM) faced challenge of vertical and horizontal well production for many shale gas plays and contributes better understanding of shale gas formation. Steel body PDC bit technology provides solution for hole cleaning challenges, penetration rate, reduced drilling cost and optimization of ROP goals. The real time LWD for shale gas reservoir improve accurate well placement, facilitate completion design and driven by cost, time and complexity in the measurements of vertical borehole and horizontal intervals. In this study, we will present distribution of shale basins worldwide and estimated reserve globally, proper selection of technology and necessary service for long-term achievement, market forecast and confident decisions. By continuously refining techniques drives enhanced economics and develop strategy provided expert technology and service in active shale play world-wide.